The narrative structure of mass effect 3 and its potential as an ESL teaching and learning tool in narrative writing - Pang, Joseph Kok Bing, 1987-; Mohamad Hassan Zakaria; Fakulti Pendidikan (2013)
Thesis (Sarjana Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2013